Relationship between brand empowerment and employee brand understanding on employees rspad pavilion kartika - Indanat Fadhilatut Toyibah (Enrichment : Journal of Management, 2023)
This research was conducted to explore the influence of variables of brand empowerment, employee brand understanding, employer brand equity, brand psychological ownership and corporate branding to know the role of employee Brand understanding on hospital employees. The contributions from this research are expected to provide the theory/science of human resource management and also provide improved quality services in the health industry sector and also positive managerial implications on organizational management. Referring to the results of previous research and empirical theories related to the process of understanding employees’ brand and all aspects related to brand empowerment, employee brand understanding, employer brand equity, brand psychological ownership and corporate branding, this research gathered data with the survey method of spreading questionnaires online using Google forms. Respondents were selected using purposive sampling. Quantitative research is conducted using the analysis of structural equation models. (SEM). Some of the findings in this study were positive effects of brand empowerment on employee brand understanding, but no impact on brand psychological ownership. Employee Brand Understanding has a positive impact on Employee Brand Equity. In contrast, brand psychological ownership does not affect employee brand equity. In addition, corporate branding has a positive impact on brand psychological ownership. This research is useful for organizations to improve the role of employees in having a sense of ownership of the brand, as well as getting employees to understand the brand of the organization to deliver positive change and improve the quality of the company’s brand image